Avaliação de uso, apropriação e integração urbana de técnicas compensatórias para o manejo de águas pluviais: estudos de caso em Ribeirão Preto - Vicente, Tiago Zanetti de (2015)
Increasing urbanization has impacted in various ways in the environment, such as changes in the hydrological cycle, increased flooding and pollution of rain origin. Soil sealing and removal of vegetation reduce infiltration and increase the volume and speed of runoff. With the questioning of the hygienists paradigms based on rapid evacuation of runoff, alternative drainage systems seek temporal rearrangement of the flow from the use of Best Management Practices and forms of rainwater management integrated with urbanization. Some Brazilian cities have public policies to encourage the deployment of alternative drainage systems, as is the case of Ribeirão Preto, a city in the state of São Paulo with a long history of problems related to the management of storm water, as floods and maintenance its source to the underground water consumption. With the inclusion of flow control requirements in the legislation, multiplied by the city storm control structures. The objective of this study is to analyze the implementation of these BMPs in urban subdivisions, from the point of view of the ownership and use of these spaces and their integration with the surroundings. From the survey of legislation and storm control structures performed in the city, were selected two installments, the Allotment Parque dos Servidores and the Condominium Quinta do Golfe, for characterization and analysis of the conditions of pre-occupation, urban design and drainage and finally, the space for BMPs. The results highlights the neglect of the management of these spaces where maintenance is precarious and the interference of the population could compromise its hydrological functions. We conclude therefore that the technical implementation of compensatory policy is an ongoing process, not just boils down to its implementation, its success is linked to urban-landscape qualification, frequent maintenance, as well as community education and involvement in the management of these spaces